Measuring Foreign Language Students' Self‐Determination: A Rasch Validation Study. Issue 3 (23rd March 2022) - Leeming, Paul; Harris, Justin
Abstract: Self‐determination theory has been applied in various educational contexts. Language learning researchers have used factor analysis and structural equation modeling to investigate measures designed for this theory, but Rasch analysis has not been conducted. The Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS) and the Language Learning Orientation Scale (LLOS) were adapted for a Japanese tertiary educational context and administered to 600 students. Rasch analysis was applied to investigate the dimensionality of the measures and functioning of individual items. Regression analyses were used to examine the relationship between motivation and performance on an English reading and listening test. Results showed that the constructs were largely unidimensional, supporting use of these measures in future research, although problems with individual items suggest that revisions should be made. Regression analyses revealed that external forms of motivation had limited impact on performance, suggesting that teachers should attempt to enhance students' internalized forms of motivation. Abstract :